Regulation of PKA activity by an autophosphorylation mechanism in Saccharomyces cerevisiae - Solari, Clara Andrea (2014)
PKA (cAMP-dependent protein kinase) activity, as well as that of other AGC members, is regulated by multiple phosphorylations of its catalytic subunits. In Saccharomyces cerevisiae, the PKA regulatory subunit is encoded by the gene BCY1, and the catalytic subunits are encoded by three genes: TPK1, TPK2 and TPK3. Previously, we have reported that, following cAMP/PKA pathway activation, Tpk1 increases its phosphorylation status. Now, in vivo genetic and in vitro experiments indicate an autophosphorylation mechanism for Tpk1. Using array peptides derived from Tpk1, we identified Ser179 as a target residue. Tpk1 is phosphorylated on Ser179 in vivo during glucose stimulus. Reduction of the activation loop Thr241 phosphorylation increases Ser179 autophosphorylation. To evaluate the role of phosphorylation on Ser179, we made strains expressing tpk1S179A or tpk1S179D as the sole PKA kinase source. Our results suggest that Ser179 phosphorylation increases the reactivity towards the substrate without affecting the formation of the holoenzyme. Phenotypic readout analysis showed that Ser179 phosphorylation increases in vivo PKA activity, reducing cell survival, stress and lifespan. Ser179 phosphorylation increases Tpk1 cytoplasmic accumulation in glucose-grown cells. These results describe for the first time that an autophosphorylation mechanism on Tpk1 controls PKA activity in response to glucose availability.